Oxygen mobility and structural phase transformation in Bi2Sr2CaCu2O8+delta measured by anelastic spectroscopy - Gimenez, JMD; Grandini, Carlos Roberto [UNESP]; Santos, Dayse Iara dos [UNESP] (Elsevier B.V., 2004)
One of the most studied ceramic superconductors for application has been, undoubtedly, Bi2Sr2CaCu2O8+delta. Although being a multiphasic material, it has proved to have great advantages compared to other ceramic systems. Measurements of the elastic energy loss and modulus (anelastic spectroscopy) as a function of temperature call distinguish among different atomic jumps that occur inside the various phases or at different local ordering. In this paper, mechanical loss spectra of Bi2Sr2CaCu2O8+delta bar shaped samples, made by a conventional method, have been measured between 80 and 600 K, using a torsion pendulum operating in frequencies below 50 Hz, for samples annealed in vacuum up to 600 K. Possible relaxation mechanisms are proposed to explain the origin of the mechanical-loss peaks observed 300 and 500 K. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: BSCCO; anelastic spectroscopy; oxygen mobility; cuprates